Correlation of Students Final Paper to Archival Scientific Development: Case Study of Archival Science Study Program, Vocational College, UGM - Arif Rahman Bramantya; Rina Rakhmawati (Record and Library Journal, 2022)
Background of the study: Student research paper have an important role in the effort to mapping scientific archival field. Scientific work in the form of a diploma student's final paper can be a representation of the real conditions of conceptual dynamics and archival practices. Therefore, this study analyzes how the relationship between student final paper and the development of archival education curriculum. Purpose: This study aims to explain the correlation of student's final paper to the scientific development of archivel science at diploma level. The approach in this study refers to descriptive analysis. Method: This study is a descriptive qualitative research The method in this study is a literature study and interviews, while the instruments used in data collection are the results of an inventory of the students final paper of the Archival Science Study Program, Vocational College, UGM from 1997-2020. The data analysis technique refers to the frequency distribution using Microsoft Excel program. Findings: The tendency of students final paper related to the study of processing and managing textual is still dominant in the field of records. In addition, the dynamics of scientific development in the archival science still refers to the practical realm to create paraprofessional graduates in their fields. Conclusion: The scientific development of archival science through discourse in an effort to develop and establish new study programs at the Diploma-3 and Diploma-4 levels is relevant, considering the needs of Arsiparis in several institutions or organizations, both in the public and private sectors. Keywords: Archival Scientific, final paper, record